Religion Teachers' Perceptions of the Abolition of the Khilafah and Jihad Teaching Materials in the Islamic Religious Education Textbook - Nugroho, Puspo; Fatah, Ahmad; Hidayat, Aat (LPPM IAIN Kudus, 2021)
This study aims to determine the perception of Fiqh teachers on changes in Khilafah material, radicalism in material content, and learning strategies for Khilafah material. The methodology employed in this research was a qualitative approach using a multistrategy, namely interviews, documentation, and observation. This study’s results revealed that at the first point regarding teachers’ perceptions of the policy, they tended to agree that there were several suggestions at the level of academic concepts, such as the need to be given a special space for Fiqh Siyasah content. Second, in the Khilafah material at Minister of Religion Decree (Keputusan Menteri Agama, KMA) Number 165 of 2014, absolutely no elements lead to radicalism. It all depended on how the teacher taught it. On the third point, it is more in the nature of adapting to the context in which Indonesia stands through discussion forums, is not rigid in using learning resources, and accommodates learning resources for the Qur’an and Hadith, Ijma’, Qiyas, Istihsan, Istishab, Maslahah Mursalah, ‘Urf, and some under the context of the Fiqh learning material.